2022
DOI: 10.3389/fendo.2022.978280
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture combined with metformin versus metformin alone to improve pregnancy rate in polycystic ovary syndrome: A systematic review and meta-analysis

Abstract: ObjectiveThe aim of this study was to evaluate the comparison between acupuncture combined with metformin versus metformin alone in improving the pregnancy rate of people with polycystic ovary syndrome (PCOS).MethodsA literature search of eight databases resulted in nine randomized controlled trials (RCTs) that assessed the effect of acupuncture combined with metformin on pregnancy rate in PCOS patients compared with metformin alone. Subsequently, data extraction and analysis were conducted to evaluate the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Among the seven included meta-analyses, acupuncture for infertility caused by PCOS, ovulation dysfunction, and anovulatory have been published in the recent 4 years (21)(22)(23)(24); the details about the seven included meta-analyses are provided in Supplementary Table S5. Except for LUFS, the number of RCTs for male infertility and female infertility caused by other diseases were less than three; therefore, we only conducted meta-analysis of acupuncture for LUFS infertility.…”
Section: Meta-analysis Of Acupuncture For Lufs Infertilitymentioning
confidence: 99%
“…Among the seven included meta-analyses, acupuncture for infertility caused by PCOS, ovulation dysfunction, and anovulatory have been published in the recent 4 years (21)(22)(23)(24); the details about the seven included meta-analyses are provided in Supplementary Table S5. Except for LUFS, the number of RCTs for male infertility and female infertility caused by other diseases were less than three; therefore, we only conducted meta-analysis of acupuncture for LUFS infertility.…”
Section: Meta-analysis Of Acupuncture For Lufs Infertilitymentioning
confidence: 99%
“…Remarkably, this treatment has shown no detrimental impact on the rate of ovulation or the likelihood of a successful live birth (Wu et al, 2020). The combination of acupuncture and metformin has demonstrated efficacy in enhancing the ovulation rate and improving the homeostatic model assessment of insulin resistance in women afflicted with PCOS as compared to the use of metformin alone (Chen et al, 2022).…”
Section: Acupuncturementioning
confidence: 99%
“…Interestingly, this systematic review suggested that acupuncture could promote the recovery of menstrual cycles as well as downregulate the levels of LH and testosterone in PCOS patients. A recent systematic review showed that acupuncture combined with metformin improved pregnancy rate, ovulation rate, and insulin resistance in PCOS patients compared to using metformin alone ( 97 ). Another study found that acupuncture combined with moxibustion improved pregnancy, ovulation, and miscarriage rates, as well as the levels of some sex hormones and metabolic indicators ( 98 ).…”
Section: Evidence-based Study Of Acupuncture For Pcosmentioning
confidence: 99%